Potential risk factors associated with diabetic mellitus in patients with Febrile upper urinary tract calculi with infection - Meng Xu; Shaoqiang Xing; Xuefeng Zhang; Yongchao Jiang; Yun Chen (PLoS ONE, 2025)
Purpose Patients with febrile upper urinary tract calculi with infection (FUUTCI) are prone to develop or have developed severe infection. This research aimed to evaluate the potential risk factors associated with diabetes mellitus (DM) in patients with FUUTCI. Materials and methods From September 2018 to December 2023, patients with FUUTCI admitted to our hospital were retrospectively studied. The patients were divided into a diabetic group (n=52) and a non-diabetic group (n=148), and the differences in demographics, etiology, infection indicators on admission, treatment, and outcome between the two groups were compared. Then regression analysis was performed for gender, stone location, occurrence of urinary sepsis, septic shock, use of pressors, bacterial multiresistance, positive fungal culture, and use of two or more antibiotics. Results Compared with non-diabetic patients (148 cases, 74.0%), diabetic patients (52 cases, 26.0%) had a higher prevalence of cardiovascular and cerebrovascular diseases (P=0.031), the rate of using two or more antibiotics (P=0.029), the positive rate of yeast culture (P=0.037), the procalcitonin value of admission or emergency (P=0.022). There was a significant difference in stone location (P=0.039). Regression analysis showed that DM was an independent risk factor for febrile urinary tract infection in patients with kidney stones compared to patients with ureteral stones (P=0.032). Conclusions In patients with FUUTCI, the risk factors associated with DM made treatment more complicated. In patients with FUUTCI and under the premise of active treatments, DM was not a risk factor for urosepsis, septic shock, use of vasoactive drugs, and infection of multi-drug resistant bacteria. Compared to patients with ureteral calculi, DM was an independent risk factor for febrile urinary tract infection in patients with kidney calculi.